CARDIOPROTECTIVE EFFECTS OF CURCUMIN AGAINST DIABETES AND NICOTINE-COMBINED OXIDATIVE STRESS - Ibrahim, Zein Shaban; Soliman, Mohamed Mohamed; Mahmoud, Shawky; Shukry, Mustafa (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Diabetic cardiomyopathy (DCM) develop through oxidative stress-induced myocardial cell apoptosis that cause cardiac tissue damage resulting in hemodynamics disturbance while Cigarette Smoking (CS) is associated with a significant increase in the risk of recurrent ventricular tachyarrhythmia in ischemic and non-ischemic cardiomyopathy patients caused by oxidative stress. Curcuma longa extract (curcumin) is known to protect against hyperglycemia-induced oxidative stress. This brought in mind to investigate the probability of the crcumin ability to ameliorate the combined diabetes and smoking induced oxidative stress caused DCMMaterials and Methods: Diabetic rats were administered nicotine to investigate the effect of the combined oxidative stress of diabetes and nicotine. Moreover, curcumin was administered to examine its protective effect on possible oxidative stress induced diabetes and nicotine.Results: Nicotine administration in a dose of 1.5 mg/kg to diabetic rats increased the oxidative stress. This occurs through elevation of plasma nitric oxide (NO) and upregulation of cardiac tissue inducible nitric oxide synthase (iNOS) and Endothelin-1 mRNA expressions, in addition to elevation of plasma triglycerides (TG), and LDL and reduction of HDL levels. Nicotine administration also reduced the cardiac tissue protective mechanism through reduction of plasma superoxide dismutase (SOD), cardiac tissue Erythropoietin (EPO), vascular endothelial growth factor (VEGF) isoforms and VEGF receptor mRNA expressions. These combined oxidative stresses were manifested by elevation of the plasma cardiac markers troponin I and creatine kinase (CK-MB). Supplementation of curcumin prevented the diabetic and nicotine-induced oxidative stress through reduction of plasma NO and iNOS and Endothelin-1 mRNA expressions to their control levels and elevation of plasma SOD and upregulation of cardiac tissue Erythropoietin (EPO), vascular endothelial growth factor (VEGF) isoforms and VEGF receptor mRNA expressions. This curcumin protective effect of the cardiac tissue was manifested by normalization of the plasma cardiac marker troponin I and CK-MB.Conclusion: These results strongly confirmed that curcumin protected cardiac tissues from the combined oxidative stress induced by diabetes and nicotine.